Heuristic approach for reactive loss reduction in a distribution network with varying loads - Garcia, Katrina A. (2004)
This paper discusses a method of reducing reactive losses using compensating capacitors in distribution network based on a heuristic approach. A heuristic approach means an iterative methodology. The developed algorithm in loss reduction covers five major tasks. he first step is to select a few critical nodes, termed the sensitive nodes. These nodes are selected by first identifying the branch with the largest reactive power. Then, the capital and costs of installing capacitors are considered. Next step is the determination of the optimal number of capacitors at a specific location in order to attain the highest monetary savings possible. The varying conditions of the loads in a year is also taken into account. Finally, the decision of whether to install or not to install compensating capacitors in the sensitive node is made. This decision is such that the net financial gain is attainable after all considerations mentioned above. The method is applied to a 45-node test feeder which is a part of the 38 feeder distribution system of the city of Windsor, Ontario. Another test system used to apply the method is the 122-node test feeder from the IEEE.